Strategi Guru Dalam Mengatasi Kejenuhan Belajar Bahasa Arab Di SMP Amanah 1 Helvetia - Saputra, Aditia; Zuliana, Zuliana (Yayasan Rahmat Islamiyah, 2024)
Learning saturation is very often found in every school both at the elementary and secondary levels. This learning saturation turns out to have a major influence on the achievement of a learning goal and even learning saturation inhibits students in understanding, interacting in the classroom, and inhibits the process of developing the quality of thinking, therefore we examine how a teacher's strategy is to overcome learning saturation in arabic language subjects. This research was conducted at junior high school AMANAH 1 Helvetia in january 2024 with qualitative methods. Boredom in learning arabic can be overcome with a combination of teacher methods and strategies in teaching supported by learning media able to overcome boredom in learning arabic at junior high school AMANAH 1 Helvetia.Â Two of the eight students who felt bored because they did not understand or felt that learning was difficult to understand even though one of them had studied arabic when they were in elementary school, teachers and students in the class were able to succeed in learning without feeling bored and bored in class by 75% with a combination of teacher strategies this result is quite appreciative researchers.